Polymorphism of IL-1β rs16944(T/C) Associated with Serum Levels of IL-1β and Subsequent Stimulation of Extracellular Matrix Degradation Affects Intervertebral Disk Degeneration Susceptibility - Wang Z; Song X; Fang Q; Xia W; Luo A (Dove Medical Press, 2021)
Zhao Wang,1 Xiaoxia Song,2 Qingbo Fang,3 Weige Xia,1 Aihua Luo2 1Department of Orthopedics, The Second Poverty Relief Hospital of Xinjiang Uygur Autonomous Region (The Fifth People′s Hospital of Xinjiang Uygur Autonomous Region), Urumqi, Xinjiang, People’s Republic of China; 2Department of Critical Care Medicine, The Second Poverty Relief Hospital of Xinjiang Uygur Autonomous Region (The Fifth People′s Hospital of Xinjiang Uygur Autonomous Region), Urumqi, Xinjiang, People’s Republic of China; 3Department of Vascular Surgery, People’s Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, People’s Republic of ChinaCorrespondence: Aihua LuoDepartment of Critical Care Medicine, The Second Poverty Relief Hospital of Xinjiang Uygur Autonomous Region (The Fifth People′s Hospital of Xinjiang Uygur Autonomous Region), No. 159, West Kashi Road, Urumqi, 830000, People’s Republic of ChinaTel +86-18116803983Email 33180536@qq.comPurpose: To investigate the association of polymorphism of IL-1β rs16944(T/C) with intervertebral disk degeneration (IDD), explore the possible mechanism and evaluate the predictive value of IL-1β for IDD.Patients and Methods: A total of 196 consecutive patients with IDD were recruited, and 196 healthy controls were matched to these patients based on sex and age (± 3 years). The polymorphisms of IL-1β rs16944(T/C), rs1143623(G/C), rs10490571(T/C) and rs2853550(A/G) were determined, and serum IL-1β, MMP-1, MMP-3, MMP-9 and a disintegrin-like and metalloproteinase with thrombospondin motif-4 (ADAMTS-4) levels were measured. Univariate analysis was performed with Student t-test or one-way ANOVA followed by post hoc and Chi-square test. Variables with two-sided P< 0.10 were included in multivariate analysis, which employed a backward stepwise logistic regression model. Receiver operating characteristic (ROC) curve was used to evaluate the predictive value.Results: Multivariate analysis showed that the polymorphism of IL-1β rs16944(T/C) was independently associated with IDD. The risk for IDD was significantly increased in TT and TC genotype compared with CC genotype, and the OR of TT genotype was higher than that of TC genotype. ANOVA analysis showed that serum concentration of IL-1β was highest in IL-1β rs16944 TT genotype, intermediate in TC genotype, and lowest in CC genotype. Similarly, serum concentrations of MMP-3 and ADAMTS-4 demonstrated the same tendency of TT > TC > CC genotype. Serum concentrations of MMP-1 and MMP-9 were higher in TT genotype than in TC and CC genotype. The area under curve (AUC) of IL-1β levels in predicting IDD was 0.788 (SE: 0.023, P=0.001, 95% CI: 0.742– 0.834), and the predictive value was modest with a sensitivity of 77.0% and a specificity of 75%.Conclusion: Polymorphism of IL-1β rs16944(T/C) affected IDD susceptibility through upregulation of serum levels of IL-1β and subsequent stimulation of ECM degradation. IL-1β levels could be applied in predicting IDD.Keywords: intervertebral disk degeneration, single-nucleotide polymorphisms, IL-1β, susceptibility, predictive value